Factors Associated with a Short (<2 Days) or Long (>10 Days) Length of Stay after Colectomy: A Multivariate Analysis of over 400 Patients. Issue 10 (October 2016) - Cologne, Kyle G.; Byers, Sean; Rosen, David R.; Hwang, Grace S.; Ortega, Adrian E.; Ault, Glenn T.; Lee, Sang W.
A prospectively maintained database of 415 patients undergoing colectomy was evaluated. We performed a logistic regression analysis to identify factors associated with 1) length of stay (LOS) of 2 days or less and 2) LOS of 10 days or more. Investigated variables included demographics, American Society of Anesthesiology (ASA) score, diagnosis, operative procedure, approach and time, transfusion requirements, and occurrence of any complications. Factors associated with a LOS of two days or less included ASA [odds ratio (OR): 0.34, 95% confidence interval (CI): 0.208–0.576], use of transversus abdominis plane block (OR: 5.259, 95% CI: 2.825–9.791), and operative time (OR: 0.98, 95% CI: 0.974–0.986). Age >65 had an OR of 1.73, though this did not reach statistical significance. Factors associated with LOS >10 days included ASA (OR: 2.152, 95% CI: 1.245–3.721), anastomotic leak (OR: 2.163, 95% CI: 1.486–3.148), ileus (OR: 8.790, 95% CI: 4.501–17.165), and surgical site infection (OR: 5.846, 95% CI: 2.764–12.362). Cancer and transfusion status were associated but did not reach statistical significance. Although operative time was longer in left-sided resections, no differences in LOS were observed. In conclusion, numerous factors are associated with short or long LOS and may help stratify resource utilization after colectomy. Further study is needed to confirm our findings.